2004
DOI: 10.1515/hf.2004.084
|View full text |Cite
|
Sign up to set email alerts
|

Artificial weathering of tropical woods. Part 1: Changes in wettability

Abstract: Changes in the wettability of eight species of tropical woods during artificial weathering up to 600 h are discussed from the aspect of chemical and structural changes in their surfaces: Amnurana acreana, Acacia auriculiformis, Dipterocarpus spp., Eucalyptus marginata, Eucalyptus robusta, Shorea spp., and Tabebuia spp. with relatively high and low specific gravity. On the whole, the wettability of specimens decreased upon irradiation up to 20 h; above that they increased. Changes in wettability during artifici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
42
2
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(55 citation statements)
references
References 2 publications
10
42
2
1
Order By: Relevance
“…Different structural and chemical changes that occur in wood surface in the effect of photochemical reactions during the weathering cause the reduction of contact angle and increasing the wettability of wood surface. Increased cellulose and hydroxyl groups in the effect of lignin degradation and its exit from wood surface are among the most important reasons (Kalinins andFeist 1993, Kishino andNakano 2004). Figure 8C and D show the wettability of oleothermally treated wood samples before and after the weathering for both beech and fir species.…”
Section: Universidad Del Bío -Bíomentioning
confidence: 99%
“…Different structural and chemical changes that occur in wood surface in the effect of photochemical reactions during the weathering cause the reduction of contact angle and increasing the wettability of wood surface. Increased cellulose and hydroxyl groups in the effect of lignin degradation and its exit from wood surface are among the most important reasons (Kalinins andFeist 1993, Kishino andNakano 2004). Figure 8C and D show the wettability of oleothermally treated wood samples before and after the weathering for both beech and fir species.…”
Section: Universidad Del Bío -Bíomentioning
confidence: 99%
“…For a comprehensive view of wood weathering, a number of studies on the general features of natural outdoor weathering, the accelerated natural weathering tests and the artificial weathering of untreated wood are available [4,41,42,[44][45][46][47].…”
Section: Weathering Tests Of Woodmentioning
confidence: 99%
“…Kishino and Nakano [45,101] investigated the changes in wettability of tropical woods for outdoor purposes during artificial weathering up to 600 h. On the whole, the wettability of specimens decreased upon exposure up to 20 h; above that, it increased. They found that the changes in wettability during artificial weathering differed depending on wood species.…”
Section: Wettability Changesmentioning
confidence: 99%
See 2 more Smart Citations